The Multilevel Mechanism of Multifoci Service Orientation on Emotional Labor: Based on the Chinese Hospitality Industry - Yong Yang (International Journal of Environmental Research and Public Health, 2020)
Emotional labor exerts a significant impact on employees’ physical and mental health as a unique form of labor. This study aims to explore the multilevel mechanism of multifoci service orientation on emotional labor from the social capital perspective. Through a multistage survey of managers and employees of 31 hospitality service companies in China, we obtained a valid sample of 31 business managers and 760 employees from hotel, restaurant, and tourism. Using Statistical analytical tools, the results revealed that organizational service orientation and individual service orientation enhanced individual social capital, which promoted employees’ deep acting and exerted a partial mediation effect on the correlation between individual service orientation and deep acting. Besides, individual social capital exerted a partial mediation effect on the relationship between organizational service orientation and deep acting. At the organizational level, organizational service orientation positively affected organizational social capital; and organizational social capital positively affected aggregate deep acting. The study results provide theoretical guidance for service companies to enhance employees’ well-being.